2006
DOI: 10.1126/science.1120392
|View full text |Cite
|
Sign up to set email alerts
|

Ion Distributions near a Liquid-Liquid Interface

Abstract: Mean field theories of ion distributions, such as the Gouy-Chapman theory that describes the distribution near a charged planar surface, ignore the molecular-scale structure in the liquid solution. The predictions of the Gouy-Chapman theory vary substantially from our x-ray reflectivity measurements of the interface between two electrolyte solutions. Molecular dynamics simulations, which include the liquid structure, were used to calculate the potential of mean force on a single ion. We used this potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
272
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(285 citation statements)
references
References 24 publications
11
272
2
Order By: Relevance
“…Here, the Gibbs energy of transfer from water to 1,2-DCE of Cl À is equal to 51 AE 4 kJ mol À1 and that of BA + equal to À67 AE 4 kJ mol À1 5 such that the potential window is limited by the transfer of chloride. When using LiSO 4 instead of LiCl, the potential window can be extended, as sulfate ions are more hydrophilic than chloride. All in all, in such a system the potential window is equal to about 1 Volt as shown in Fig.…”
Section: Polarised Itiesmentioning
confidence: 99%
“…Here, the Gibbs energy of transfer from water to 1,2-DCE of Cl À is equal to 51 AE 4 kJ mol À1 and that of BA + equal to À67 AE 4 kJ mol À1 5 such that the potential window is limited by the transfer of chloride. When using LiSO 4 instead of LiCl, the potential window can be extended, as sulfate ions are more hydrophilic than chloride. All in all, in such a system the potential window is equal to about 1 Volt as shown in Fig.…”
Section: Polarised Itiesmentioning
confidence: 99%
“…4 The average ion distribution in the vicinity of a charged surface is often described using the Poisson-Boltzmann theory, 5,6 a mean-field approximation treating ions implicitly as an ion cloud. The theory neglects fluctuations and correlations, the finite size of ions, and the discreteness of solvent, and therefore has obvious restrictions; pronounced deviations from its predictions emerge at the limit of high ion concentrations, [7][8][9] as well as in the presence of large surface charge densities or multivalent ions. [10][11][12][13][14] We note that there are a number of theories that go beyond the Poisson-Boltzmann approximation.…”
Section: Introductionmentioning
confidence: 99%
“…ex (8) which, when nondimensionalized by 2qen B , is given by (13) Closing the LDA description requires a form for the excess chemical potentials μẽ x ± , after which the LDA equations can be solved self-consistently by imposing constraints on the electrostatic potential at the charged interface (14) and in the bulk…”
Section: Electric Double-layer Modelsmentioning
confidence: 99%
“…Despite these well-known shortcomings, LDA models have been proposed to treat shortranged enthalpic 20 and steric interactions between equisized 21,22 and asymmetric 23 ions for ionic liquids, 24 electrochemical cells, 6,13 and liquid−liquid interfaces. 8,10 We recently showed that all EDLs described by any particular LDA have self-similar scaling and thus collapse onto a single master curve when plotted against suitably derived similarity coordinates. 25 Such similarity coordinates can be derived directly from experimentally or computationally determined EDL profiles, without assuming any particular form for a LDA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation